High Dietary Inflammatory Index Is Associated With Increased Plaque Vulnerability of Carotid in Patients With Ischemic Stroke. Issue 10 (October 2020) - Peng, Min; Wang, Ling; Xia, Yaqian; Tao, Lei; Liu, Yujing; Huang, Feihong; Li, Shun; Gong, Xiuqun; Liu, Xinfeng; Xu, Gelin
Abstract : Background and Purpose: Long-term dietary patterns can influence the intensity of systemic inflammation and, therefore, the development of atherosclerosis. This study aimed to evaluate the association between dietary inflammatory index (DII) and vulnerability characteristics of carotid atherosclerotic plaques in patients with ischemic stroke. Methods: Patients with ischemic stroke within 7 days of onset were enrolled. DII was calculated from 32 food components with the help of a food frequency questionnaire. Vulnerable plaque was defined as presence of artery positive remodeling (remodeling index >1.1) and low CT attenuation plaques (<35 HU) on carotid arteries by computed tomography angiography. Results: Of the 398 enrolled patients, 144 (36.2%) were detected with vulnerable plaque. Their DII ranged from −4.58 to 4.18. Patients with vulnerable plaques consumed less nutrients with anti-inflammatory properties, less fruits and vegetables (85.6±64.3 versus 94.6±74.4 g/d, P =0.027), and less nuts (5.66±7.14 versus 8.84±15.9 g/d, P =0.024) than patients without vulnerable plaques. Patients with vulnerable plaque had higher DII than patients without vulnerable plaque (−0.26±1.54 versus −0.64±1.53, P =0.018). Logistic regression analysis revealed that DII was associated with vulnerable plaques after adjusted for major confounding factors (odds ratio=1.307; 95% CI, 1.113–1.533). Conclusions: DII is associated with the vulnerability of carotid plaques in patients with ischemic stroke. Considering a possible causal relationship, the mechanisms underlying the association between diet and atherosclerosis warrant further study. Abstract : Supplemental Digital Content is available in the text.